Degradation of Labor Rights in the Era of Omnibus Law: An Analysis of the Implications of Regulation on Workers' Welfare and Protection - T. Hija Gunawan; Irmayadi Sastra; Cindy Tan (Walidem Institute and Publishing, 2026)
Objective: This study aims to critically analyze the degradation of labor rights in Indonesia during the Omnibus Law era, focusing on its implications for worker welfare and protection, particularly how it affects job security, wages, and workers' social rights. Theoretical framework: The theoretical framework of this study is rooted in social justice theory, legal protection theory, and industrial relations theory. These frameworks emphasize the state's responsibility to ensure basic workers' rights, secure employment, fair wages, and a balanced relationship between workers, employers, and the government. Literature review: The literature review highlights that previous studies have primarily concentrated on the economic and investment dimensions of labor laws, with limited exploration of the social, humanitarian, and normative consequences. There is a lack of comprehensive research addressing the broader impacts of labor rights erosion, particularly in relation to worker welfare and protection. Methods: This study employs a qualitative research design based on a literature review. Secondary data sources are utilized, including scientific journals, laws and regulations, Constitutional Court decisions, labor organization reports, and relevant policy documents. Results: The findings reveal that the Omnibus Law not only simplifies regulatory frameworks but also shifts the focus of labor protection towards economic flexibility. This shift leads to reduced severance pay, increased outsourcing without sectoral boundaries, uncertainty regarding employment status, potential declines in wages, and the erosion of leave rights and social protections. These changes undermine workers' bargaining power, increase their vulnerability to exploitation, and negatively affect mental health, economic stability, and human dignity. Implications: This study highlights the need for a comprehensive evaluation of labor regulations, stronger state oversight, and a restructured labor policy that balances investment interests with worker protection. Novelty: The study’s novelty lies in its approach, viewing the Omnibus Law not just as an economic tool but as a social justice issue, emphasizing the real-life experiences of workers impacted by these changes.